Work strain in midlife and 28-year work ability trajectories - von Bonsdorff, Monika E.; Kokko, Katja; Seitsamo, Jorma; von Bonsdorff, Mikaela B.; Nygård, Clas-Håkan; Ilmarinen, Juhani; Rantanen, Taina (Scandinavian Journal of Work, Environment & Health, 2011)
' ' OBJECTIVES ': 'We investigated the 28-year development trajectories of work ability among initially middle-aged male and female municipal employees and the association of perceived mental and physical work strain in midlife by work ability trajectory groups. ' ' METHODS ': 'The baseline data of the Finnish longitudinal study of municipal employees (FLAME) were collected in 1981 (N=6257) with follow-ups in 1985, 1992, 1997, and 2009. Work ability was assessed in all the waves as present perceived work ability relative to lifetime best. Altogether, N=2690 had work ability data in 1981 and 2009, and at least for one wave in between these years, and were included in group-based semi-parametric mixture modeling trajectory analyses. Baseline differences in mental and physical work strain according to the work ability trajectories were assessed with MANCOVA (multivariate analysis of covariance). ' ' RESULTS ': 'A five-group work ability trajectory model was identified for men and a four-group model for women. For the majority, a linear decline from excellent to moderate or moderate to poor work ability was observed while non-linear trajectories with sudden collapse and, in some cases, modest subsequent recovery of work ability were also observed. Individuals who maintained their work ability on an excellent-to-moderate level throughout the follow-up more often reported low mental and physical work strain in midlife. ' ' CONCLUSIONS ': 'A substantial proportion of individuals seem to maintain their work ability on a moderate level from midlife to old age. Work strain may have far-reaching negative effects on individuals’ work ability from midlife to old age, warranting vigilance in maintaining and promoting work ability throughout the lifespan.
Keywords: ageing; development trajectory; mental work strain; physical work strain; work ability; work strain